PENGARUH PENGGUNAAN MEDIA MANIPULATIF PADA PEMBELAJARAN MATEMATIKA TERHADAP HASIL BELAJAR SISWA DI KELAS V SEKOLAH DASAR - Ranjani, Dwi Selvia; Tampubolon, Budiman; Sabri, Tahmid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe study aimed to determine the effect of using manipulative media on student learning outcomes in mathematics subjects in the fifth grade of East Pontianak 10 Elementary School. The method used is an experiment with a form of research that is Quasi Experimental Design with the experimental design of Nonequivalent Control Group Design. Using a population sample because they use 2 classes, namely class V A and V B number 61. Research instruments to measure student learning outcomes in the form of tests of Mathematics questions. Data collection techniques use measurement techniques. The research obtainedÂ the average post-test of the control class was 66.76 and the average post-test of the experimental class was 79.84. Hypothesis test results using t-test obtained t_count = 3.284 for dk = 59 and Î± = 5% obtained t_table = 2.001, which means t_count (3.284)> t_table (2.001), then Ha is accepted. So, it can be concluded that there are differences in student learning outcomes at the pretest and posttest. From the results of the calculation of the effect size Â 0.779 (medium). Thus learning by using manipulative media in the form of cardboard paper has a influence on mathematics at State Elementary School 10 East Pontianak.Keywords: Learning Outcomes,Manipulative Media, Mathematics Learning